Genomic and functional diversity of the human-derived isolates of Faecalibacterium - Li, Wenxi; Lin, Xiaoqian; Liang, Hewei; Wu, Zhinan; Wang, Mengmeng; Sun, Jingxi; Li, Xiaofang; He, Wenxin; Gao, Xiaowei; Hu, Tongyuan; Xiao, Liang; Zou, Yuanqiang (Frontiers in Microbiology, 2024)
Faecalibacterium is one of the most abundant bacteria in the gut microbiota of healthy adults, highly regarded as a next-generation probiotic. However, the functions of Faecalibacterium genomes from cultured strains and the distribution of different species in populations may differ among different sources. We here performed an extensive analysis of pan-genomes, functions, and safety evaluation of 136 Faecalibacterium genomes collected from 10 countries. The genomes are clustered into 11 clusters, with only five of them were characterized and validly nomenclated. Over 80% of the accessory genes and unique genes of Faecalibacterium are found with unknown function, which reflects the importance of expanding the collection of Faecalibacterium strains. All the genomes have the potential to produce acetic acid and butyric acid. Nine clusters of Faecalibacterium are found significantly enriched in the healthy individuals compared with patients with type II diabetes. This study provides a comprehensive view of genomic characteristic and functions and of culturable Faecalibacterium bacterium from human gut, and enables clinical advances in the future.